The Influence of Parental Support, Income Expectations, and Entrepreneurship Education on Entrepreneurial Intentions: Entrepreneurship Motivation as a Mediation Variabel: (Study of Students in Solo Raya) - Yoppi Syahrial; Indri Sri Endarwati; Gustita Arnawati Putri (International Journal of Economics, Management and Accounting, 2024)
Instead of being in good condition when experiencing a demographic bonus, it turns out that Indonesia has not been able to maximize this factor and is still hampered by unemployment and the government is always encouraging the formation of new entrepreneurs. This research examines the factors that can influence entrepreneurial intentions among students in Soloraya, namely parental support, income expectations, entrepreneurial education and entrepreneurial motivation which have a dual role as direct influences and mediation. The current research aims to harmonize the theory of planned behavior to explain the role of parental support, income expectations and entrepreneurial motivation in current conditions. This research involved 250 students spread across several universities in Solo and analyzed the data using smart PLS. The results found in this research were that all the variables studied were able to influence students' entrepreneurial intentions in Solo Raya.